Pengaruh Tax Amnesty, Pengetahuan Perpajakan, dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Bekasi Utara - Fifin Arifianti; Rifani Siti Hariyanti Manurung; Dadang Abdul Mukti (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to determine the effect of tax amnesty, tax knowledge, and service quality on individual taxpayer compliance. The type of research used is quantitative. The population of this study is an individual taxpayer registered at the KPP North Bekasi The number of samples used in this study were 100 respondents using the Slovin formula with the Incidental Sumpling method. The data  collection  technique  used  in  this  study  is  multiple  linear regression and using SPSS statistic 24. The results of this study indicate that the effect of tax amnesty has an effect on individual  taxpayer compliance by 30.6%, tax knowledge has an influence on individual taxpayer compliance. by 31.9%, and the quality of service has an influence on individual taxpayer compliance by 44.0%. So that tax amnesty, tax knowledge, and service quality have a significant effect on individual taxpayer compliance in North Bekasi KKP. Based on the results of the analysis conducted, it shows that there is a positive influence on Tax Amnesty, Tax Knowledge, and Service Quality. The variables of tax amnesty, tax knowledge, and service quality affect the individual taxpayer compliance variable simultaneously with a value of 63.8%, where 36.2% is influenced by other variables not examined in this study.This study aims to determine the effect of tax amnesty, tax knowledge, and service quality on individual taxpayer compliance.The type of research used is quantitative. The population of this study is an individual taxpayer registered at the KPP North Bekasi.The number of samples used in this study were 100 respondents using the Slovin formula with the Incidental Sumpling method. Thedata  collection  technique  used  in  this  study  is  multiple  linear regression and using SPSS statistic 24. The results of this study indicate that the effect of tax amnesty has an effect on individual  taxpayer compliance by 30.6%, tax knowledge has an influence on individual taxpayer compliance. by 31.9%, and the quality of service has an influence on individual taxpayer compliance by 44.0%. So that tax amnesty, tax knowledge, and service quality have a significant effect on individual taxpayer compliance in North Bekasi KKP. Based on the results of the analysis conducted, it shows that there is a positive influence on Tax Amnesty, Tax Knowledge, and Service Quality. The variables of tax amnesty, tax knowledge, and service quality affect the individual taxpayer compliance variable simultaneously with a value of 63.8%, where 36.2% is influenced by other variables not examined in this study.